Once more on the so-called ‘Felstreppentunnel’ in the Armenian Highlands - Dan, Roberto (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The present article is aimed to discuss the problem of the dating of the ‘stepped rock-cut tunnels’, also known in the literature by the German term ‘Treppentunneln’ or ‘Felstreppentunnel’. The last section is dedicated to further thoughts on the problems involved in dating most of the Urartian archaeological remains currently known, from a wider perspective.